The Impact of Internal Bulletins on Information Needs in Balai Besar Wilayah Sungai Brantas - Sukarya, Sella Desita; Kristiyono, Jokhanan (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2023)
Mass communication is undoubtedly constructive for humans to meet their information needs individually and in groups. Communication is essential in human life as a process of delivering messages. It is the most basic need that is closely related to the continuity and defense of the existence of an organization or company. One of the roles in helping to establish effective communication relationships with the use of internal media has also been carried out by the Brantas. Using internal media implemented by the Brantas can establish relationships between internal and external stakeholders and assist in synchronizing information. The purpose was to determine the use of internal bulletins by employees in meeting internal information needs, to determine the fulfillment of internal information needs obtained by employees from internal bulletins as a source of information, and to determine the effect of using internal bulletins to meet the internal information needs of employees at Balai Besar Sungai Brantas. The result is that it was found that there was a relationship between the use of the Brantas Bulletin to meet their needs and the use of internal media could be used by an organization or agency.